Statistical analyses in Swedish randomised trials on mammography screening and in other randomised trials on cancer screening: a systematic review. (November 2015) - Autier, Philippe; Boniol, Mathieu; Smans, Michel; Sullivan, Richard; Boyle, Peter
Objectives: We compared calculations of relative risks of cancer death in Swedish mammography trials and in other cancer screening trials. Participants: Men and women from 30 to 74 years of age. Setting: Randomised trials on cancer screening. Design: For each trial, we identified the intervention period, when screening was offered to screening groups and not to control groups, and the post-intervention period, when screening (or absence of screening) was the same in screening and control groups. We then examined which cancer deaths had been used for the computation of relative risk of cancer death. Main outcome measures: Relative risk of cancer death. Results: In 17 non-breast screening trials, deaths due to cancers diagnosed during the intervention and post-intervention periods were used for relative risk calculations. In the five Swedish trials, relative risk calculations used deaths due to breast cancers found during intervention periods, but deaths due to breast cancer found at first screening of control groups were added to these groups. After reallocation of the added breast cancer deaths to post-intervention periods of control groups, relative risks of 0.86 (0.76; 0.97) were obtained for cancers found during intervention periods and 0.83 (0.71; 0.97) for cancers found during post-intervention periods, indicating constant reduction in the risk of breast cancer death during follow-up, irrespective of screening. Conclusions: The use of unconventional statistical methods in Swedish trials has led to overestimation of risk reduction in breast cancer death attributable to mammography screening. The constant risk reduction observed in screening groups was probably due to the trial design that optimised awareness and medical management of women allocated to screening groups.